Algal-based hollow fiber membrane bioreactors for efficient wastewater treatment: a comprehensive review - Javed, Muhammad Uzair; Mukhtar, Hamid; Zieniuk, Bartłomiej; Rashid, Umer (Multidisciplinary Digital Publishing Institute, 2024)
The treatment of living organisms is a critical aspect of various environmental and industrial applications, ranging from wastewater treatment to aquaculture. In recent years, algal-based hollow fiber membrane bioreactors (AHFMBRs) have emerged as a promising technology for the sustainable and efficient treatment of living organisms. This review provides a comprehensive examination of AHFMBRs, exploring their integration with algae and hollow fiber membrane systems for diverse applications. It also examines the applications of AHFMBRs in various areas, such as nutrient removal, wastewater treatment, bioremediation, and removal of pharmaceuticals and personal care products. The paper discusses the advantages and challenges associated with AHFMBRs, highlights their performance assessment and optimization strategies, and investigates their environmental impacts and sustainability considerations. The study emphasizes the potential of AHFMBRs in achieving enhanced nutrient removal, bioremediation, and pharmaceutical removal while also addressing important considerations such as energy consumption, resource efficiency, and ecological implications. Additionally, it identifies key challenges and offers insights into future research directions. Through a systematic analysis of relevant studies, this review aims to contribute to the understanding and advancement of algal-based hollow fiber membrane bioreactors as a viable solution for the treatment of living organisms.